Impact of Brace Fracture on Column Splice Demands in Braced Frames - Faytarouni, Mahmoud; Şeker, Onur; Akbaş, Bülent; Shen, Jay (Asce-Amer Soc Civil Engineers, 2020)
Braces made of square hollow structural sections (HSSs) in special concentrically braced frames (SCBFs) are likely to fracture under expected demand levels. This study, therefore, examines the additional seismic demands on column splices induced due to brace fracture. First, the study introduces the brace fracture models that were utilized for predicting fractures of square HSSs. Second, the selected 5-story and 13-story SCBFs with two different splice locations permitted in the seismic design practice were assessed under an ensemble of ground excitations by introducing different fracture prediction models. Third, the splice demands in terms of axial force, bending moment, and their combined effects were discussed with and without considering brace fracture. The study finds that brace fracture has a negligible impact on tensile force demands on column splices. In return, flexural demands, and the combined tensile force and flexural demands, are shown to be strongly influenced by brace fracture. It is also shown that the splices in SCBFs are vulnerable to undergo inelastic deformations when a brace fracture occurs, which is against the intended design objective. (c) 2020 American Society of Civil Engineers.
Keywords: Modeling brace fracture; Postbuckling seismic performance; Special concentrically braced frames; Column splices; Nonlinear dynamic analysis; Seismic demands